Positions constructed in specialist health care for patients experiencing intimate partner violence - Koistinen, Inka (2012)
The aim of this study was to examine the positions that health personnel in specialist health care construct for patients experiencing intimate partner violence. It was also studied whether these constructed positions were challenged by other health care professionals and if so, how. The method of analysis chosen was discourse analysis.